2019
DOI: 10.1002/jlb.ma0718-296r
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying NK cell growth and survival changes in response to cytokines and regulatory checkpoint blockade helps identify optimal culture and expansion conditions

Abstract: NK cells are innate lymphocytes critical for immune surveillance, particularly in eradication of metastatic cancer cells and acute antiviral responses. In contrast to T cells, NK cell‐mediated immunity is rapid, with spontaneous cytotoxicity and cytokine/chemokine production upon pathogen detection. The renaissance in cancer immunology has cast NK cell biology back into the spotlight with an urgent need for deeper understanding of the regulatory networks that govern NK cell antitumor activity. To this end, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 66 publications
(127 reference statements)
3
14
0
Order By: Relevance
“…During extended stimulation, IL-15 was the main driver of proliferation, whereas IL-12 inhibited proliferation in this in vitro setting devoid of antigen (Extended Data Fig. 6c), in contrast to MCMV infection 25 , consistent with previous studies 40,41 . Together, these studies highlight a division of labor across cytokine conditions that support NK cell activity; however, additional conditions present in vivo are required to fully optimize their effector potential.…”
Section: Combined Cytokine Cocktail Best Correlates With Early Infection In Vivosupporting
confidence: 90%
“…During extended stimulation, IL-15 was the main driver of proliferation, whereas IL-12 inhibited proliferation in this in vitro setting devoid of antigen (Extended Data Fig. 6c), in contrast to MCMV infection 25 , consistent with previous studies 40,41 . Together, these studies highlight a division of labor across cytokine conditions that support NK cell activity; however, additional conditions present in vivo are required to fully optimize their effector potential.…”
Section: Combined Cytokine Cocktail Best Correlates With Early Infection In Vivosupporting
confidence: 90%
“…Murine splenic NK cells were exposed to heparin and assayed for cell proliferation kinetics as previously described [ 12 , 31 ]. Interestingly, while heparin does not appear to affect NK cell division rates ( Figure 2 A), using total cohort number analysis to estimate survival of NK cells [ 31 ], we observed that heparin was able to enhance the survival of NK cells in vitro ( Figure 2 B).…”
Section: Resultsmentioning
confidence: 99%
“…Murine splenic NK cells were exposed to heparin and assayed for cell proliferation kinetics as previously described [ 12 , 31 ]. Interestingly, while heparin does not appear to affect NK cell division rates ( Figure 2 A), using total cohort number analysis to estimate survival of NK cells [ 31 ], we observed that heparin was able to enhance the survival of NK cells in vitro ( Figure 2 B). Addition of heparin in cell cultures for enhanced manufacturing of NK cell products has previously been considered [ 36 ] as it is an effective replacement for stroma [ 37 ], and this might be because of the survival stimulus that we showed here.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Invitrogen) as described 79 . Briefly, NK cells were resuspended at no more than 2 × 10 AAVS1, IKZF1, IKZF2, Synthego) was formed and mixed together with NK cells and Cas9 enhancer, followed by electroporation (4D-Nucleofector X Unit, Lonza) 80 .…”
Section: Nk Cell Proliferation Assaymentioning
confidence: 99%